Processing and Properties of Textured Potassium Strontium Niobate (KSr2Nb5O15) Ceramic Fibers - Texture Development - Alkoy, Sedat; Dursun, Sinan (Wiley, 2012)
Highly [001] textured KSr2Nb5O15 (KSN) ceramic fibers were fabricated by a combination of novel alginate gelation method and templated grain growth using acicular KSr2Nb5O15 template particles. The needle-like KSN template particles were prepared by molten salt synthesis method with salt/powder ratio of 2 giving the highest aspect ratio. Fibers were extruded into CaCl2 salt solutions from alginate-based slurries without or with 10 wt% KSN template particles using a nozzle with 2 mm diameter and 80 mm length. Varying sintering temperature from 1300 degrees C to 1450 degrees C and time from 2 to 6 h were found to increase the texture. A maximum degree of orientation, f(00l), of 0.95 was obtained, as measured by Lotgering factor, and a grain orientation distribution, r, of 0.28 was obtained as measured by rocking curve analysis.
Keywords: Templated Grain-Growth; Molten-Salt Synthesis; Orientation; Fabrication; Gelation; Particles